Grading, staging and Nottingham prognostic index scoring of breast carcinoma - A Pradhan; P Paudyal; AK Sinha; CS Agrawal (Association of Clinical Pathologists of Nepal, 2017)
Background: Breast carcinoma is the most frequent malignant tumor in women accounting for approximately 15% of female cancer deaths. It is the second most common malignancy among women in Nepal. Our objectives were to study the extent and spread of different histological types breast carcinoma in the eastern region of Nepal, to grade and stage the tumors, score the prognosis. Materials and Methods: A cross-sectional descriptive study of mastectomy specimens with axillary lymph node sampling was done for a period of two years. Diagnosis was done using WHO classification. Modified Bloom Richardson score and TNM system was used to grade and stage the tumors. Nottingham Prognostic index was applied to score the prognosis. Results: Out of 31 total cases, the most common histologic type was Invasive Carcinoma of No Special Type (67.74%). The largest tumor size was of 12cm which had poor NPI score. Most tumors were of grade II and T2. Out of 30 cases with lymph nodes, 13 were negative for metastasis pN0, 10 were pN1 and 7 were pN2. Extranodal spread was observed in 6 out of 17 cases with lymph node metastasis and was associated with higher grades and poor prognosis. Conclusion: Higher grade tumors, lymph node metastasis and extranodal extension are associated with higher Nottingham Prognostic Index score.